Rolling Locomotion Control of a Biologically Inspired Quadruped Robot Based on Energy Compensation. (5th October 2015) - Nemoto, Takuma; Elara Mohan, Rajesh; Iwase, Masami
Abstract : We have developed a biologically inspired reconfigurable quadruped robot which can perform walking and rolling locomotion and transform between walking and rolling by reconfiguring its legs. This paper presents an approach to control rolling locomotion with the biologically inspired quadruped robot. For controlling rolling locomotion, a controller which can compensate robot's energy loss during rolling locomotion is designed based on a dynamic model of the quadruped robot. The dynamic model describes planar rolling locomotion based on an assumption that the quadruped robot does not fall down while rolling and the influences of collision and contact with the ground, and it is applied for computing the mechanical energy and a plant in a numerical simulation. The numerical simulation of rolling locomotion on the flat ground verifies the effectiveness of the proposed controller. The simulation results show that the quadruped robot can perform periodic rolling locomotion with the proposed energy-based controller. In conclusion, it is shown that the proposed control approach is effective in achieving the periodic rolling locomotion on the flat ground.